The Reality of applying Critical Thinking Skills by Social Studies Teachers in Their Classrooms and Its Relationship with Some Variables in the First Stage of Basic Education (Journal of Hama University, 2019)
The study aimed to identify  the reality of applying Critical Thinking Skills in the First Stage of Basic Education by Social Studies teachers.  It also seeked to identify the effect of the variables of gender, scientific qualification and experience of the teacher in Aleppo. To achieve the objectives of the study, the researcher developed a questionable which consisted of (25) items. The study sample included (89) teachers of the First Stage of Basic Education. The results showed that the level of applying Critical Thinking Skills  was generally moderate. Besides, the results showed the absence of statistically significant differences in the level of applying Critical Thinking Skills according to the variables of gender and academic qualification, while the results showed the existence of statistically significant differences in the level of applying Critical Thinking Skills according to the experience of the teacher. In light of the results of the study, the researcher offered a number of recommendations, including: providing training courses for teachers on the importance of Critical Thinking Skills and the necessity of implementing it in the classroom, developing school curricula to meet the needs of students and creating an appropriate school environment for practicing Critical Thinking Skills .